Stabilization of a multimode He-Ne laser: A vivid demonstration of thermal feedback. - Tobin, Roger G.; Stanek, Ferdinand.; Foiles, C.L. (Tufts University. Tisch Library., 2017)
A thermal stabilization technique for multimode He-Ne laser tubes is demonstrated. Intensity stability of ∼1% is achieved, where the intensity of the unstabilized laser varied by more than a factor of 5. The system provides both a dramatic demonstration of the principle of negative feedback and a stimulating introduction to basic electronics, laser physics, and solid state physics. It is simple enough to be constructed as an undergraduate laboratory project.